The Interest of Beauty Vocational High School Students to Study in Higher Education - Maisya putri jasri; Mimi Yupelmi (Fakultas Pariwisata dan Perhotelan Universitas Negeri Padang, 2023)
This research is motivated by the number of Beauty Vocational School students in West Sumatra who have low interest in continuing their education at the Department of Make-up and Beauty at the Faculty of Tourism and Hospitality. It is influenced by internal factors and external factors. This study aims to 1) determine the interest of SMK Negeri Beauty students in West Sumatra to continue the Makeup and Beauty Education Study Program at the Faculty of Tourism and Hospitality in terms of internal factors (Attention, Feelings of Pleasure and Strength of Motives). Then in terms of external factors (teachers, parents and peers). The type of research used is quantitative research. The research subjects were STUDENTS of the Beauty Vocational High School in West Sumatra. Meanwhile, the object of the research is the factors that influence students' interest in continuing their education in the Department of Make-up and Beauty at the Faculty of Tourism and Hospitality. The sampling technique in this study is proportional random sampling. Data collection techniques using a questionnaire. The implementation of the questionnaire trial to the respondents of the trial was 217 people. The data in this study were analyzed by statistical analysis. The data in terms of internal factors were already in moderate interpretation. Then in terms of external factors, it is already in moderate interpretation.